Positive solutions of Schrödinger-Kirchhoff-Poisson system without compact condition - Fengxia Liu (Boundary Value Problems, 2017)
Abstract Purpose The existence of positive solutions for a class of nonlinear Schrödinger-Kirchhoff-Poisson systems. Methods Variational method. Results Some results on the existence of positive solutions.